HUBUNGAN POLA ASUH ORANG TUA DENGAN KEMANDIRIAN ANAK USIA PRA SEKOLAH DI TK BUNDA JAMBI - Suryati suryati (Jurnal Akademika Baiturrahim Jambi, 2016)
Background: The influence of parents in helping children develop independence and discipline of children. The linkage parenting parents in laying the basics of discipline and independence to the child and help develop it so that children have self-discipline and have independence. Independence is an important aspect of child development for the nurse in order to provide holistic nursing care to children.Method:This study uses the type of analytic research which is to know the Relationship Pattern Parent Parenting With Self-Reliance Pre School Children In TK Bunda Jambi. The population is all parents have a chield  with 81 students. Total Sampling is 81 children.. Data collection was done by questionnaire, data. Analyse data with bivariate. Result:The result of research about parenting relationship with children independence obtained p-value 0.003 (<0.05) which means there is a meaningful relationship between parenting and independence of children in TK Bunda Kota Jambi Year 2014. It is expected that health workers can provide health education to teachers and parents of preschool children about parenting to support the development of child self-reliance.